Study of paediatric systemic lupus erythematosus in tertiary care center in South India - S., Shashidhara V.; H., Anil Kumar; Kariyappa, Mallesh (International Journal of Contemporary Pediatrics, 2020)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by multisystem inflammation and the presence of circulating autoantibodies directed against self-antigens. The reported prevalence of SLE in children and adolescents (1-6/100,000) is lower than that in adults (20-70/100,000). The study among pediatric population were few and hence this study from south India was undertaken. Objective of this study was to study the clinical and immunological profile of children with systemic lupus erythematosus (SLE). To study the Distribution of Renal Lesions according to ISN/RPS Classification of Lupus Nephritis Methods: Retrospective hospital based observational study in tertiary level centre in Bengaluru (BMCRI). Medical records of children with SLE admitted in Pediatric department from the period of 2010-2019 through the hospital information system were analyzed. Clinico pathological features and immunological profile were compared with other studies. Results: Among 25 patients studied male to female ratio was1:2.5. The mean patient’s age at the time of presentation was13.2 year, the youngest child being 7 year. The mean duration of disease before diagnosis was 1year, most common systems involved were haematological (92%), followed by kidney (88%), GIT (72%), mucocutaneous (68%) cases. 19 (91%) cases were ANA positive and two ANA negatives. Anti-ds DNA was positive in 18(85%) patients, 5 were anti smith antibody positive. Diffuse proliferative glomerulonephritis (ISN/RPS class IV) was the most commonly seen histological pattern, seen in 9(56%) patients, 4(25%) patient had focal and segmental proliferative glomerulonephritis (ISN/RPS class III) and 2(12%) had membranous glomerulonephritis (grade ISN/RPS class V). Conclusions: SLE can present with diverse, unpredictable clinical manifestations, the primary diagnosis can often be missed if the index of suspicion is not high, since childhood SLE does not present with classical manifestations.